Ways to improve the operation process off roller-die press-granulators - Komar, Artem; Комар, Артем Станіславович (Запоріжжя : ТДАТУ, 2024)
EN: The results of research on resource conservation and energy efficiency of complex technological processes widely used in industry have shown that in the agro-industrial complex one of the technological processes that meets the criteria of resource conservation and energy efficiency is press granulation. In press granulators, agricultural raw materials are processed in the production of granulated compound feed and their individual components, in the production of fuel pellets from agricultural waste, and also for the purpose of obtaining granulated intermediate products. At the same time, press granulation is an energyintensive process, and the relevance of its improvement is quite high. One of the feasible ways to improve the press granulation process is to develop new and optimize existing designs of press granulators. Main research materials. In Ukraine and abroad, roller-matrix press granulators are most common. One of the feasible ways to improve the press granulation process is to develop new and optimize existing designs of press granulators. However, a review of scientific sources gives reason to believe that over the past twenty years, the designs although domestic and foreign ring die pressing mechanisms have reached a higher technical level, their structural features have changed insignificantly. (advance) between the matrix and each of the pressing rollers, it follows that the working process of all existing and newly designed ring die pellet mills is characterized by lateral extrusion of the product. Lateral extrusion – the movement of the material in the direction of the ends of the working bodies and its extrusion beyond the contact area - is especially pronounced in the lagging zone and less intense in the extrusion zone into the die dies. The intensity of the transverse flow of the material is determined by its stress state in the wedgeshaped space, and also depends significantly, like the stress state itself, on a number of factors: structural and mechanical (rheological) properties of the processed product (yield limits under compression, contact friction coefficient), design parameters of the pellet mill.
Keywords: energy efficiency is press granulation; the production of fuel pellets; agricultural waste